Histo - chemical mechanism of defense in barley roots attacked by Fusarium graminearum - KUMAR*, J. (Indian Phytopathology, 2008)
Comparative microscopy of inoculated and non - inoculated roots of resistant and susceptible barley genotypes revealed cell wall appositions (CWAs) in rhizodermal cells and accumulation of hydrogen peroxide (H2 O2 ) in cortical cells as defense - related components against Fusarium graminearum (Fg), the incitant of common root rot. Resistant genotype Chevron exhibited significantly higher quantities of these defence components than the susceptible genotype Uschi. Temporal and spatial manifestation of CWAs as well as accumulation of H2 O2 were directly related with lesser colonization of Fg hyphae in root tissues of Chevron as compared to Uschi. Data based on bright field microscopy suggested that CWAs in rhizoderm and H2 O2 accumulation in cortical cells are involved as components contributing for resistance that is characterized as a slow rate of mycelial growth after successful penetration. During the course of present investigations, we pioneered the procedures of root microscopy for studying histo - chemical response of barley roots to infection of Fg. These procedures may be further employed to discern the mechanism of host resistance against a wide variety of Fusarium species infecting roots of several agricultural and horticultural crops.